Victims of crime Acts in Slovakia (Does it fulfil minimum european requirementS?) - Kováčová, Zuzana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The attempt to reduce the risk of secondary and repeat victimisation, of intimidation and of retaliation by the offender done in the article. As wide a range of measures as possible should be made available to practitioners to prevent distress to the victim during court proceedings in particular as a result of visual contact with the offender, his or her family, associates or members of the public.